Exploring the binding mechanism of Ginsenoside Rd to Bovine Serum Albumin: Experimental studies and computational simulations. Issue 13 (3rd November 2022) - Lin, Jialiang; Tang, Min; Meti, Manjunath D.; Liu, Yong; Han, Qingguo; Xu, Xu; Zheng, Yuan; He, Zhendan; Hu, Zhangli; Xu, Hong
Abstract: The interaction of bovine serum albumin (BSA) with Ginsenoside Rd (GSRd) was studied using multiple spectroscopic methods, isothermal titration calorimetry (ITC), molecular docking and density functional theory (DFT) calculation. The fluorescence experiments showed that GSRd quenched BSA intrinsic fluorescence via a static quenching process because of the formation of the GSRd-BSA complex. UV-visible and circular dichroism (CD) spectral studies indicated that the binding of GSRd to BSA resulted in the loosening and unfolding of BSA backbone, with the loss of partial α-helix structures. Also, thermodynamic parameters obtained from ITC experiment suggested that BSA-binding of GSRd was a spontaneous endothermic reaction driven by entropy, and that hydrophobic interactions were the main forces within the BSA-GSRd complex. Additionally, docking studies and DFT calculation further implied that hydrogen bonds also helped stabilize the GSRd-BSA system. These research results could help us better understand the pharmacokinetic behavior of GSRd, and provide useful conformational change information of BSA induced by the bound drugs, to the design of analogues drugs with more effective pharmacological properties. Graphical Abstract: UF0001